A Simple Fused‐Ring Acceptor toward High‐Sensitivity Binary Near‐Infrared Photodetector. Issue 12 (7th April 2022) - Deng, Suinan; Zhang, Lianjie; Zheng, Jingbo; Li, Ji; Lei, Shuyi; Wu, Zuhao; Yang, Dezhi; Ma, Dongge; Chen, Junwu
Abstract: Near‐infrared organic photodetector of high sensitivity is essential for various remote sensing applications. In this work, a new simple fused‐ring acceptor "NTQ" with a narrow optical bandgap of 1.11 eV is designed and synthesized to demonstrate the first near‐infrared organic photodetector example featuring a non‐fused A‐D‐A′‐D‐A molecular framework. The optimized geometry of NTQ exhibits high planarity and the relevant pristine film shows high electron mobility of 1.51 × 10 −4 cm 2 V −1 s −1 . Moreover, the PTB7‐Th:NTQ blend can achieve relatively high and balanced hole/electron mobility even though the photo‐active layer thickness is up to 320 nm. The NTQ‐based devices exhibit high shot‐noise‐limited specific detectivity ( D sh *) of 3.72 × 10 12 Jones at 1000 nm under the bias of –0.1 V and a board D sh * response over 10 12 Jones from 320 to 1070 nm. Furthermore, the device exhibits fast averaged rise and fall times of 2.02 and 2.42 µs, respectively. This work demonstrates that molecular engineering with the A‐D‐A′‐D‐A framework can endow near‐infrared photo‐active materials with high‐performing photodetectors for wide applications. Abstract : Newly developed simple fused‐ring acceptor "NTQ" with A‐D‐A′‐D‐A framework and narrow bandgap of 1.11 eV exhibits broad and high detectivity of over 10 12 Jones in the range of 300–1070 nm with a maximum detectivity at 1000 nm. The binary organic photodetector exhibits an excellent linear dynamic range of up to six orders of magnitude under a 980 nm laser.